Cancer-related cognitive impairment in non-CNS cancer patients: Targeted review and future action plans in Europe. (December 2022) - Sleurs, Charlotte; Amidi, Ali; Wu, Lisa M.; Kiesl, David; Zimmer, Philipp; Lange, Marie; Rogiers, Anne; Giffard, Benedicte; Binarelli, Giulia; Borghgraef, Cindy; Deprez, Sabine; Duivon, Mylène; et al.
Abstract: Cancer-related cognitive impairment (CRCI) has increasingly been identified over the last two decades in non-CNS system cancer patients. Across Europe, researchers have contributed to this effort by developing preclinical models, exploring underlying mechanisms and assessing cognitive and quality of life changes. The ultimate goal is to develop interventions to treat patients experiencing CRCI. To do so, new challenges need to be addressed requiring the implementation of multidisciplinary research groups. In this consensus paper, we summarize the state of the art in the field of CRCI combined with the future challenges and action plans in Europe. These challenges include data sharing/pooling, standardization of assessments as well as assessing additional biomarkers and neuroimaging investigations, notably through translational studies. We conclude this position paper with specific actions for Europe based on shared scientific expert opinion and stakeholders involved in the Innovative Partnership for Action Against Cancer, with a particular focus on cognitive intervention programs. Graphical Abstract: ga1 Highlights: Cancer-related cognitive impairments (CRCI) are increasingly studied in Europe. A multidisciplinary approach is needed to disentangle contributing factors to CRCI. Ultimately, cognitive interventions are being developed based on ongoing science. The ECCC aims to gain knowledge in this field to optimize oncological treatment.